2006
DOI: 10.1197/j.aem.2006.06.049
|View full text |Cite
|
Sign up to set email alerts
|

Rescuer Fatigue: Standard versus Continuous Chest‐Compression Cardiopulmonary Resuscitation

Abstract: CCC-CPR resulted in more adequate compressions per minute than STD-CPR for the first 2 minutes of CPR. However, the difference diminished after 3 minutes, presumably as a result of greater rescuer fatigue with CCC-CPR. Overall, CCC-CPR resulted in more total compressions per minute than STD-CPR during the entire 9 minutes of resuscitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 62 publications
1
56
0
1
Order By: Relevance
“…A single manikin study (LOE 5) 222 demonstrated that medical students performed better-quality chest compressions during the first 2 minutes of continuous chest compressions compared with 15:2 CPR, although there was deterioration in quality after 2 minutes. An LOE 5 manikin study 223 of HCPs showed that the number of effective compressions (depth Ͼ38 mm) was the same if the rescuer changed every minute or every 2 minutes during 8 minutes of continuous chest compressions.…”
Section: Rescuer Fatiguementioning
confidence: 99%
“…A single manikin study (LOE 5) 222 demonstrated that medical students performed better-quality chest compressions during the first 2 minutes of continuous chest compressions compared with 15:2 CPR, although there was deterioration in quality after 2 minutes. An LOE 5 manikin study 223 of HCPs showed that the number of effective compressions (depth Ͼ38 mm) was the same if the rescuer changed every minute or every 2 minutes during 8 minutes of continuous chest compressions.…”
Section: Rescuer Fatiguementioning
confidence: 99%
“…(6) Several manikin studies have revealed that BLS quality drops significantly during the first two minutes, especially the depth of compression, even when verbal feedback was provided in case of decreased compression depth. (7)(8)(9)(10)(11)(12)(13) These studies offer sophisticated insight into the process of BLS in terms of physical capabilities of providers. However, we still do not have the answers to the following questions: Do subjective parameters positively correlate with objective ones?…”
Section: Discussionmentioning
confidence: 99%
“…흉부압 박을 시행하는 구조자는 쉽게 피로해지게 되고 그로인해 서 충분한 흉부압박의 속도와 깊이를 유지하지 못하는 경우가 많은데 [11][12][13], 흉부압박 시행 후 1분이 경과하면 흉부압박의 깊이가 감소하고 [12], 병원 외에서 시행된 심 폐소생술에 대한 임상적 관찰실험에 따르면, 구조자의 힘 이 빠졌을 경우에 부적절한 흉부이완이 더욱 높았다 [14]. 2) 흉부압박 대 인공호흡의 비율을 맞추어 반복 연구 가 필요하겠다.…”
Section: 선행 연구결과들을 보면 흉부압박을 시행할 때에 전 체 심폐소생술 기간 중에 흉부압박 중단시간의 비율이unclassified